Witnessed sleep apneas together with elevated plasma glucose are predictors of COPD exacerbations - Ingebrigtsen, Truls S. (Eur Clin Respir J, 2020)
OBJECTIVE: Sleep apnea and elevated plasma glucose associates with inflammation which associates with the risk of COPD exacerbations. We investigated the risk of exacerbations in individuals with COPD, witnessed sleep apneas, and elevated plasma glucose. METHODS: From the Copenhagen City Heart Study cohort, we identified 564 individuals with COPD (forced expiratory volume in 1 sec divided by forced vital capacity, FEV(1)/FVC<0.70), no asthma, above 40 years of age, and more than 10 pack-years of smoking history, with information on witnessed apneas and levels of plasma glucose. We prospectively recorded hospital admissions with COPD exacerbations during maximum available follow-up (26.3 years; mean 10.7 years). Cox-regression analyses were used to analyze the risk of COPD exacerbations. RESULTS: We identified 74 (13%) individuals with sleep apnea without elevated plasma glucose, 70 (12%) had elevated plasma glucose (above 6.9 mM (>125 mg/dL)) without sleep apnea and 11 individuals had the presence of both conditions. In univariable analysis, witnessed apneas together with elevated plasma glucose had a high risk of exacerbations, hazard ratio (HR) = 5.81 (2.34–14.4, p = 0.0001) compared to those without sleep apnea and without elevated plasma glucose. Multivariable analysis, adjusting for several risk factors of exacerbations, showed a similar result, HR = 3.45 (1.13–10.5, p = 0.03). Both presence of sleep apnea without elevated plasma glucose and the presence of elevated plasma glucose without sleep apnea showed no associations with the risk of exacerbations. CONCLUSIONS: Witnessed sleep apneas in COPD are associated with increased risk of exacerbations, but only among those with elevated plasma glucose.